2017
DOI: 10.1007/s10067-017-3619-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients treated for giant cell arteritis: a case-control study

Abstract: The objective of the study was to assess the quality of life (QOL) of patients with giant cell arteritis (GCA), following high dose of corticosteroids (CS). Thirty patients with GCA who had stopped CS or who were under long-term low dose of CS were included and matched to 60 controls. QOL was measured by the SF-36 score and a specific questionnaire. GCA patients had no impairment of QOL compared to controls according to SF-36. Most of them (57%) estimated that their general condition was improved following tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…Though a qualitative study performed in the UK also found that anxiety about future visual loss was an important concern of GCA patients [23], this is in contrast to other studies. Jobard et al and Kupersmith et al found that GCA visual complications did not have any major impact on health-related quality of life (QoL), as assessed using the SF-36 score [24,25]. However, neither of the aforementioned studies distinguished between patients with and without visual symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though a qualitative study performed in the UK also found that anxiety about future visual loss was an important concern of GCA patients [23], this is in contrast to other studies. Jobard et al and Kupersmith et al found that GCA visual complications did not have any major impact on health-related quality of life (QoL), as assessed using the SF-36 score [24,25]. However, neither of the aforementioned studies distinguished between patients with and without visual symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…As we appreciate that vision ranks as the number one concern among patients with GCA [24], our study used the VF-14 [26] as a measure of visual function among GCA subjects. Expectedly, GCA patients with current visual symptoms had lower (worse) VF-14 score than those without visual symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Die Lebensqualität wird aus Sicht der Betroffenen durch die Angst vor Visusverlust und anderen ischämischen Komplikationen sowie vor Nebenwirkungen der GC-Therapie bestimmt. Sie gleicht sich gesunden Kontrollen an, wenn eine anhaltende Remission unter niedrig dosierten oder ausgeschlichenen GC erreicht werden kann [124].…”
Section: üBergeordnetes Prinzip C (Starker Konsens)unclassified
“…Fears surrounding potential vision loss and dissatisfaction with the adverse effects of glucocorticoids were identified as the most important HRQOL concerns in a survey of patients with GCA [11], but vision loss was not associated with impaired HRQOL at baseline or after treatment with glucocorticoids with or without methotrexate in an RCT that enrolled too few patients for a treatment effect to be investigated [12]. In a case-control study, HRQOL was not impaired in patients with GCA either before or after glucocorticoid treatment compared with controls [13], though this study examined only HRQOL data after high-dose glucocorticoid treatment had been discontinued (the 30 patients in the analysis had either stopped corticosteroid treatment or were taking long-term low doses of glucocorticoids).…”
Section: Introductionmentioning
confidence: 99%